The Value of Family Education from the Perspective of Local Wisdom in Malay Proverbs: Inquisitive Semantic Study - Lisdawati; Nurhasni; Hermandra (Raja Zulkarnain Education Foundation, 2026)
Malay proverbs constitute an important part of oral cultural heritage that not only preserves the collective experiences of society but also functions as a medium for transmitting life values across generations. One proverb that remains widely used in daily communication is the apple does not fall far from the tree (buah jatuh tidak jauh dari pohonnya). This expression is commonly employed to describe similarities between children and their parents in terms of behavior, habits, and character. Beyond its simple usage, however, the proverb reflects the Malay cultural perspective that positions the family as the primary environment for shaping individual identity and character. This study examines the meaning of the proverb buah jatuh tidak jauh dari pohonnya through an inquisitive semantics approach by exploring its lexical, grammatical, contextual, cultural, and inquisitive meanings. The study applies a qualitative descriptive method using literature review and textual analysis. The research data consist of the linguistic unit of the selected Malay proverb, which is analyzed in relation to its cultural context and family education values. The findings reveal that the proverb does not merely express intergenerational resemblance but also contains essential family educational values, including role modeling, parental responsibility, value transmission, self-awareness, and hope for future generations. These findings indicate that Malay proverbs remain relevant as a form of local wisdom that can contribute to strengthening character education within the family context.